2021
DOI: 10.1101/2021.07.22.453322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteome Profiling of Cerebrospinal Fluid Reveals Novel Biomarker Candidates for Parkinson’s Disease

Abstract: Parkinson's disease (PD) is a growing burden worldwide, and despite ongoing efforts to find reliable biomarkers for early and differential diagnosis, prognosis and disease monitoring, there is no biofluid biomarker used in clinical routine to date. Cerebrospinal fluid (CSF) is collected often and should closely reflect structural and functional alterations in PD patients' brains. Here we describe a scalable and sensitive mass spectrometry (MS)-based proteomics workflow for CSF proteome profiling to find specif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…The authors also found significant correlations between depression and the same CSF inflammatory markers, as well as an association between lower cognitive scores and higher serum amyloid A in the CSF [ 61 ]. Proteomic studies in CSF have also shown an increase of HLA proteins (HLA-DRA, HLA-DRB1 and HLA-DPA1) [ 63 ] in familial PD patients (LRRK2 G2019S carriers) versus controls, providing further evidence of increased inflammation in PD.…”
Section: Age-related Immune Changes In Parkinson’s Diseasementioning
confidence: 99%
“…The authors also found significant correlations between depression and the same CSF inflammatory markers, as well as an association between lower cognitive scores and higher serum amyloid A in the CSF [ 61 ]. Proteomic studies in CSF have also shown an increase of HLA proteins (HLA-DRA, HLA-DRB1 and HLA-DPA1) [ 63 ] in familial PD patients (LRRK2 G2019S carriers) versus controls, providing further evidence of increased inflammation in PD.…”
Section: Age-related Immune Changes In Parkinson’s Diseasementioning
confidence: 99%